Status of Engagement and Commitment of Faculty Members in Extension Services in BulSU External Campuses: Basis for an Action Plan - Sierto, Maricel E.; Navarro, Ricky J. (Future Science / FSH-PH Publications, 2023)
The main objective of this study is to determine the level of commitment of external campus faculty members to the implementation of extension services. In particular, this study sought answers to the following questions: (1) What is the demographic profile of the respondents in terms of gender, employment status, years in service, years in doing extension, and number of extension involvement? (2) What is the level of engagement of faculty members in external campuses in conducting extension services? (3)What is the level of commitment of faculty members in external campuses in conducting extension services? (4) What action plan may be developed to improve the involvement of faculty members in external campuses in conducting extension services? This study used a descriptive study using a questionnaire to collect relevant data. The results show that (1) More female faculty members provide extensions compared to male faculty members. Full-time faculty must provide extension services as one of their primary responsibilities; irregular may collaborate with permanent faculty. Because tenured faculty are aware of their core responsibilities, they must commit hours of extension activities even when they are available for teaching responsibilities. Regular faculty continue to be committed to extension services. (2) Faculty members show great appreciation in providing extension services and considering the efforts of the partner community because they believe that they are their potential partners in community development. (3) Faculty members provide extension services not only for accreditation purposes, but also to promote sustainable development, especially in marginalized areas.